AI-assisted writing in EFL education: Students’ experiences with Quillbot - Suryanto Suryanto; Nuriyati Islami; Turki Alsolami; Bolormaa Shinjee (Universitas Ahmad Dahlan, 2026)
This study investigates undergraduate EFL students’ experiences using QuillBot in academic writing contexts. Employing a qualitative descriptive approach, the researchers conducted in-depth interviews with six students who regularly integrated QuillBot into their writing practices. The findings revealed three major themes: strategic use of QuillBot throughout the writing process, challenges encountered during its use, and emerging pedagogical innovations related to AI-assisted writing. First, students used QuillBot strategically during planning, drafting, revising, and editing to paraphrase sentences, improve grammatical accuracy, enrich vocabulary, and enhance textual coherence. Second, despite its benefits, students experienced several challenges, including meaning distortion, overly formal expressions, overreliance on AI-generated suggestions, and reduced personal writing voice. Third, the findings highlighted pedagogical innovation in AI-assisted writing, as QuillBot contributed to increased writing confidence, improved linguistic accuracy, reduced writing anxiety, and greater writing efficiency. The study also emphasized the importance of AI literacy training, ethical guidelines, and lecturer support to promote critical, reflective, and responsible use of AI-assisted writing tools in EFL learning contexts.